2020
DOI: 10.1111/nph.16778
|View full text |Cite
|
Sign up to set email alerts
|

PuHox52‐mediated hierarchical multilayered gene regulatory network promotes adventitious root formation inPopulus ussuriensis

Abstract: Adventitious root (AR) formation is critically important in vegetative propagation through cuttings in some plants, especially woody species. However, the underlying molecular mechanisms remain elusive. Here, we report the identification of a poplar homeobox gene, PuHox52, which was induced rapidly (within 15 min) at the basal ends of stems upon cutting and played a key regulatory role in adventitious rooting. We demonstrated that overexpression of PuHox52 significantly increased the number of ARs while suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 72 publications
2
41
2
Order By: Relevance
“…PuHOX52 gene expression was induced by exogenously applied MeJA, but was significantly reduced when treated with a JA biosynthesis inhibitor, confirming its role in AR development downstream of CO1-mediated JA signaling. Wei et al (2020) also showed that PuMYC2 was a target gene of PuHox52 , and PuMYC2 - OE lines showed a significantly higher number of ARs, whereas PuMYC 2- SRDX lines produced fewer ARs than the wild type. These results show that MYC2 acts as a positive regulator in AR formation in Populus ussuriensis .…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 88%
See 1 more Smart Citation
“…PuHOX52 gene expression was induced by exogenously applied MeJA, but was significantly reduced when treated with a JA biosynthesis inhibitor, confirming its role in AR development downstream of CO1-mediated JA signaling. Wei et al (2020) also showed that PuMYC2 was a target gene of PuHox52 , and PuMYC2 - OE lines showed a significantly higher number of ARs, whereas PuMYC 2- SRDX lines produced fewer ARs than the wild type. These results show that MYC2 acts as a positive regulator in AR formation in Populus ussuriensis .…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 88%
“…Recently, Wei et al (2020) showed that the gene PuHox52 , from the HD-Zip I transcription factor family, is a positive regulator of AR development downstream of JA in Populus ussuriensis ( Figure 1 ). PuHox52 was consistently upregulated at different time points after cutting, and its overexpression significantly enhanced the number of ARs, whereas in RNAi transgenic lines the number of ARs decreased, thus confirming its role in promoting AR formation.…”
Section: Endogenous Factors Influencing Rooting Of Cuttingsmentioning
confidence: 99%
“…The GL3 downstream genes are either directly or indirectly regulated by GL3. A top-down Gaussian graphical model (GGM) algorithm was employed to find the genes that were likely to be directly regulated by GL3 (Lin, Li et al 2013, Wei 2019, Wei, Liu et al 2020). From the 146 GL3 downstream genes, the algorithm first identified 93 GL3 responsive genes that had high concordance in expression levels with gl3 expression with the expression data from the dT1, dT2, and EV RNA-seq experiments ( Supplemental Data Set 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on expression patterns, direct and indirect regulations are distinguishable with dedicated computational algorithms. The top-down GGM algorithm, with the input of a short time-course data, had been shown to separate the directly from indirectly regulated genes with more than 90% accuracy (Wei, 2019; Lin et al, 2013) and about 80% accuracy for RNA-Seq data from stably transgenics lines (Wei et al, 2020). In this study, no time-course data were generated.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors are the main players in regulatory modules controlling auxin gradients, positional information, and polarity field development, resulting in a cross-regulatory network that is involved in organ formation [37]. Several groups of transcription factors regulate key developmental processes in adventitious root formation, such as plant growth regulator-responsive transcription factors or transcription factors from WRKY, NAM/ATAF/CUC (NAC), APETALA2 (AP2), HOMEODOMAIN-LEUCINE ZIPPER (HD-ZIP I), GIBBERELLIC-ACID INSENSITIVE, REPRESSOR of GAI and SCARECROW (GRAS) and WUSCHEL, as well as WUSCHEL-related HOMEOBOX families [10,11,13,15,16,29,[38][39][40][41][42]. The expression of genes coding for transcription factors involved in stem-cell identity is a common feature during the induction of somatic embryogenesis and organogenesis [9], and the induction of transcription factors related to meristematic programs may be associated with the capacity for adventitious rooting in tree species [43].…”
Section: Transcriptional Regulation Of Adventitious Root Formationmentioning
confidence: 99%